ANALISIS FAKTOR EKSTERNAL DAN INTERNAL TERHADAP PENYALURAN KREDIT PERBANKAN DI INDONESIA (Studi Kasus Bank Umum) - Cahyaning P, Wanda Annisa (Jurnal Ilmiah Mahasiswa FEB, 2016)
The  existence  of  credit  as  a  source  of  capital  has  a  close  relationship  with  economic  growth. Unfortunately,  the  credit  growth  of  recent  years  continue  to  weaken.  The  weakening  of  credit  growth  is influenced  by  factors  of  banking  own  and  factors  beyond  the  control  of  banking,  namely macroeconomic conditions.  This  study  raised  about  how  much  influence  of  external  factors  and  internal  factors  of  the Commercial  Bank  lending  as  banks  that  manage  more  than  90%  Third  Party  Funds  across  Indonesia. External factors used were BI rate, exchange rate and economic growth. While the internal factors that Net-performing loans (NPLs) and Third Party Fund (TPF).  This  study  used  a multiple  regression  analysis with  the  data  period  from  January  2009  to  June  2014. Based on  the research results  that external  factors, BI Rate has a significant negative effect on commercial bank  lending,  exchange  rate  and  economic  growth  have  a  significant  positive  effect  on  commercial  bank lending.  While  the  internal  factors,  Net-performing  loans  (NPLs)  has  no  significant  positive  effect  on commercial bank lending. While Third Party Fund (TPF) has positive and significant impact on commercial bank lending. Kata kunci: Kredit, Bank Umum, BI Rate, Kurs, Pertumbuhan ekonomi,  NPL.